Difficulties in diagnosing the cause of hyponatraemia in an extremely premature boy - Bryłka, Aleksandra; Bjanid, Omar; Korlacki, Wojciech; Nowak, Maria; Nowak, Marta; Sobecka, Marcela; Jaszczura, Majka; Adamczyk, Piotr; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2018)
We present the history of a nine-month-old male infant born prematurely with extremely low birth weight, who was admitted to the paediatric nephrology department with dehydration, acute kidney injury, hyponatraemia, hyperkalaemia, and metabolic acidosis. While the crucial first step in the diagnosis of hyponatraemia includes the assessment of the patient’s fluid status, we focus in the discussion on the causes, diagnosis, and treatment of hypovolemic hyponatraemia. With the notable exception of congenital adrenal hyperplasia (CAH) and other primary adrenal diseases, in which there is a deficiency in aldosterone synthesis, many other salt-losing disorders share the common feature of inducing secondary hyperaldosteronism. In the presented case hyponatraemia was caused by NEC-related ileostomy with, typically, hyperkalaemia despite secondary hyperaldosteronism. The clinical picture can be very similar to pseudohypoaldosteronism type 1 (PH 1), with the renal handling of sodium being the key differentiating feature.